Trematode infection affects shell shape and size in Bulinus tropicus. (August 2022) - Hammoud, Cyril; Kayenbergh, Annelies; Tumusiime, Julius; Verschuren, Dirk; Albrecht, Christian; Huyse, Tine; Van Bocxlaer, Bert
Abstract: Trematodes can increase intraspecific variation in the phenotype of their intermediate snail host. However, the extent of such phenotypic changes remains unclear. We investigated the influence of trematode infection on the shell morphology of Bulinus tropicus, a common host of medically important trematodes. We focused on a snail population from crater lake Kasenda (Uganda). We sampled a single homogeneous littoral habitat to minimize the influence of environmental variation on shell phenotype, and barcoded snails to document snail genotypic variation. Among the 257 adult snails analysed, 99 tested positive for trematode infection using rapid-diagnostic PCRs. Subsequently we used high-throughput amplicon sequencing to identify the trematode (co-)infections. For 86 out of the 99 positive samples trematode species delineation could discriminate among combinations of (co-)infection by 11 trematode species. To avoid confounding effects, we focused on four prevalent trematode species. We performed landmark-based geometric morphometrics to characterize shell phenotype and used regressions to examine whether shell size and shape were affected by trematode infection and the developmental stage of infection (as inferred from read counts). Snails infected by Petasiger sp. 5, Echinoparyphium sp. or Austrodiplostomum sp. 2 had larger shells than uninfected snails or than those infected by Plagiorchiida sp. Moreover, the shell shape of snails infected solely by Petasiger sp. 5 differed significantly from that of uninfected snails and snails infected with other trematodes, except from Austrodiplostomum sp. 2. Shape changes included a more protuberant apex, an inward-folded outer apertural lip and a more adapically positioned umbilicus. Size differences were more pronounced in snails with 'late' infections (>25 days) compared to earlier-stage infections. No phenotypic differences were found between snails infected by a single trematode species and those harbouring co-infections. Further work is required to assess the complex causal links between trematode infections and shell morphological alterations of snail hosts. Graphical abstract: Image 1 Highlights: Trematode infections are linked to Bulinus tropicus shell shape and size variations. Variations in shell phenotype are trematode species-dependant. Trematode infections were analysed using diagnostic PCRs and amplicon sequencing. Snail shell morphology was analysed using landmark-based geometric morphometrics.